2020
DOI: 10.31025/2611-4135/2020.13939
|View full text |Cite
|
Sign up to set email alerts
|

Silver Recovery From End-of-Life Photovoltaic Panels

Abstract: The growth of the photovoltaic sector has stood out among renewable sources of energy, due to technological innovations that have brought about cost reductions. Thus, this paper aimed to analyze the technical feasibility of silver recovery from photovoltaic cells using acid leaching, followed by an evaluation of the chemical and electrochemical precipitation processes to analyze their efficiencies. As a primary objective of this work, the gravimetric composition and the metal concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The goal of this step is the selective extraction of silver over other metals. Many researchers have found that HNO 3 shows good performance in the selective dissolution of silver over tin and lead [29,[76][77][78]. After leaching, the samples were filtered and dried; subsequently, leaching experiments were conducted with glycine.…”
Section: Multivariate Design Of Experimentsmentioning
confidence: 99%
“…The goal of this step is the selective extraction of silver over other metals. Many researchers have found that HNO 3 shows good performance in the selective dissolution of silver over tin and lead [29,[76][77][78]. After leaching, the samples were filtered and dried; subsequently, leaching experiments were conducted with glycine.…”
Section: Multivariate Design Of Experimentsmentioning
confidence: 99%
“…Some of its alloys, i.e., silver-copper, are used in computer manufacturing. Silver is used in high-tech industries (i.e., electrical connectors), electronics, products for health care, photovoltaics cell production [1,2], button cells [3], and several nanomaterial industries [4][5][6][7]. Silver is used in light reflection industries for mirrors and photographic films (and X-ray films) because of its sensitivity to light and in photochromic lens manufacturing [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that there is a serious need to find a low-cost, effective and sustainable method for recovering silver (with a high efficiency) from leachates, wastewater, effluents, waste materials or other secondary resources. Several techniques have been used for reducing the silver concentration; i.e., electrodeposition methods have been used [1,17,18] and solvent extraction techniques have been used for recovering silver from highly concentrated solutions [19][20][21]. Extraction from low-grade solutions is performed through chelating composites [16,22], ion-exchange resins [23][24][25][26] and biosorbents [27][28][29].…”
Section: Introductionmentioning
confidence: 99%